TASHKENT AND FERGANA MAQOMS: ORIGINS, AESTHETIC MEANING AND CONTEMPORARY INTERPRETATION - Aslanov Sherzodjon Turgunovich (Modern American Journals, 2025)
The musical tradition of Central Asia represents a multidimensional landscape where poetry, spirituality, philosophy and artistry are woven into one unique cultural system. Among these traditions, maqom holds a special place as a sophisticated classical genre which preserves the historical memory and musical thinking of the Uzbek cultural world. While maqom remains a common heritage for the entire region, specific schools such as the Shashmaqom of Bukhara or the Khorezm maqoms developed their characteristic stylistic features. The Tashkent and Fergana maqoms, in particular, form a distinct regional tradition that demonstrates a combination of lyrical sensitivity, philosophical reflection and subtle melodic beauty. The aim of this paper is to examine the Tashkent–Fergana maqoms by exploring their historical roots, structural features, poetic foundations and contemporary relevance. Special attention will also be paid to the cultural meanings embedded in the performance tradition, as well as the challenges of preserving authenticity in a rapidly modernising environment.
Keywords: Tashkent–Fergana Maqoms; Uzbek classical music; modal system; Central Asian culture; traditional performance; poetic interpretation; Intangible Cultural Heritage; regional identity; oral transmission; musical aesthetics; maqom structure; spirituality in music.